2012
DOI: 10.1055/s-0032-1325499
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines and Good Clinical Practice Recommendations for Contrast Enhanced Ultrasound (CEUS) in the Liver – Update 2012

Abstract: Initially, a set of guidelines for the use of ultrasound contrast agents was published in 2004 dealing only with liver applications. A second edition of the guidelines in 2008 reflected changes in the available contrast agents and updated the guidelines for the liver, as well as implementing some non-liver applications. Time has moved on, and the need for international guidelines on the use of CEUS in the liver has become apparent. The present document describes the third iteration of recommendations for the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
296
3
19

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(321 citation statements)
references
References 152 publications
(193 reference statements)
3
296
3
19
Order By: Relevance
“…Finally, patients with chronic hepatitis, hepatic cirrhosis or severe fatty liver will make liver lesions difficult to detect on conventional ultrasound. [35][36][37][38] In the current study, pre-treatment conventional ultrasound showed that inconspicuous lesions accounted for 64.3% of all the lesions confirmed by CECT/CEMRI, thus conventional ultrasound-guided RFA is not suitable for them. Instead, guidance by other imaging modalities or referral to other treatment methods had to be carried out.…”
Section: Discussioncontrasting
confidence: 51%
“…Finally, patients with chronic hepatitis, hepatic cirrhosis or severe fatty liver will make liver lesions difficult to detect on conventional ultrasound. [35][36][37][38] In the current study, pre-treatment conventional ultrasound showed that inconspicuous lesions accounted for 64.3% of all the lesions confirmed by CECT/CEMRI, thus conventional ultrasound-guided RFA is not suitable for them. Instead, guidance by other imaging modalities or referral to other treatment methods had to be carried out.…”
Section: Discussioncontrasting
confidence: 51%
“…CEUS provides a technique with superb sensitivity from early arterial phase up to late venous enhancement in dynamic realtime vascular imaging. For the first time, this ultrasound technology allows the non-invasive demonstration of blood flow of inner organs at a microcirculatory level [1,2]. Further, the purely intravascular microbubbles enable ultrasound to be used to monitor changes in the blood flow of tumors and in inflamed areas in a diagnostic approach but also for therapy control.…”
Section: This Issue Of Clinical Hemorheology and Microcirculation Is mentioning
confidence: 99%
“…Further, the purely intravascular microbubbles enable ultrasound to be used to monitor changes in the blood flow of tumors and in inflamed areas in a diagnostic approach but also for therapy control. Its performance without any requirement for ionizing radiation and with no nephrotoxicity makes it a compelling choice in many clinical arenas and is now FDA approved for liver imaging, and also for children [1][2][3][4][5][6][7][8].…”
Section: This Issue Of Clinical Hemorheology and Microcirculation Is mentioning
confidence: 99%
See 2 more Smart Citations